Neuroserpin, a crucial regulator for axogenesis, synaptic modelling and cell–cell interactions in the pathophysiology of neurological disease - Godinez, Angela; Rajput, Rashi; Chitranshi, Nitin; Gupta, Veer; Basavarajappa, Devaraj; Sharma, Samridhi; You, Yuyi; Pushpitha, Kanishka; Dhiman, Kunal; Mirzaei, Mehdi; Graham, Stuart; Gupta, Vivek (Cellular and molecular life sciences : CMLS, 2022)
Neuroserpin is an axonally secreted serpin that is involved in regulating plasminogen and its enzyme activators, such as tissue plasminogen activator (tPA). The protein has been increasingly shown to play key roles in neuronal development, plasticity, maturation and synaptic refinement. The proteinase inhibitor may function both independently and through tPA-dependent mechanisms. Herein, we discuss the recent evidence regarding the role of neuroserpin in healthy and diseased conditions and highlight the participation of the serpin in various cellular signalling pathways. Several polymorphisms and mutations have also been identified in the protein that may affect the serpin conformation, leading to polymer formation and its intracellular accumulation. The current understanding of the involvement of neuroserpin in Alzheimer’s disease, cancer, glaucoma, stroke, neuropsychiatric disorders and familial encephalopathy with neuroserpin inclusion bodies (FENIB) is presented. To truly understand the detrimental consequences of neuroserpin dysfunction and the effective therapeutic targeting of this molecule in pathological conditions, a cross-disciplinary understanding of neuroserpin alterations and its cellular signaling networks is essential.